Perancangan Sistem Monitoring Pendistribusian Liquefied Petroleum Gas Berbasis Android - Pipin Yulanda (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2022)
Setya Tani Dirgantara is a company engaged in the distribution of Liquefied Petroleum Gas (LPG Gas). As an agent of LPG, PT. Setya Tani Dirgantara distributes 3 Kilogram Elpiji Gas to various sub-distributors (bases) by relying on the sending crew (drivers). However, with the large number of existing sub-distributors, it makes the Agent Administrator fast in the reporting process to the Leader. Due to the distribution reporting process from the driver to the Agent Administrator who still uses a written system, the Agent Administrator cannot get information regarding the distribution process in real-time, this of course takes a lot of time. Therefore, an idea emerged to design an android-based LPG Gas distribution monitoring system. The method used is the waterfall model or what is often called the waterfall method and the data collection techniques used are direct observation, interviews, and literature study. It is hoped that this system can assist in the process of distributing LPG gas such as monitoring distribution, payment, and reporting on the distribution of LPG gas. Keywords: Monitoring System, Distribution, Waterfall, Liquefied Petroleum Gas, LPG Gas